Disappearing halophytes and saline habitats in changing environment of SW Slovakia - Fehér, Alexander (Ecological Questions, 2011)
As a result of changes in land use, the ecologists and botanists already give details only of degradation, ruderalisation and fragmentation of halophytic plant communities (Camphorosmetum annuae, Limonio-Artemisietum santonici etc.) and the decline of halophytes on those sites (missing grazing, ploughing away, hydro-amelioration etc.).